2017
DOI: 10.1080/17565529.2017.1411240
|View full text |Cite
|
Sign up to set email alerts
|

Understanding smallholder farmers' capacity to respond to climate change in a coastal community in Central Vietnam

Abstract: Climate change as expressed by erratic rainfall, increased flooding, extended droughts, frequency tropical cyclones or saline water intrusion, poses severe threats to smallholder farmers in Vietnam. Adaptation of the agricultural sector is vital to increase the resilience of smallholder farmers' livelihoods in times of climate change. To complement efforts already implemented by farmers to reduce social vulnerability it is important to understand how farmers perceive their current and future capacity to adapt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 44 publications
3
31
1
5
Order By: Relevance
“…Many farmers indicate strong concerns related to their ability to learn from other farmers, adhering to a kind of communal knowledge, as it were. So AMs are applied in relation to their familiarity with local knowledge and group experience of the geographical features of their environment [100]. A strong social network is a prominent feature of the "Co Tu" people, and it helps them in their cultural survival.…”
Section: From Perception To Adaptive Measures Regarding the Soil Erosmentioning
confidence: 99%
See 3 more Smart Citations
“…Many farmers indicate strong concerns related to their ability to learn from other farmers, adhering to a kind of communal knowledge, as it were. So AMs are applied in relation to their familiarity with local knowledge and group experience of the geographical features of their environment [100]. A strong social network is a prominent feature of the "Co Tu" people, and it helps them in their cultural survival.…”
Section: From Perception To Adaptive Measures Regarding the Soil Erosmentioning
confidence: 99%
“…The provision of tailor-made courses and training, as well as the mediated communication between peers, friends, neighbors, cooperatives, etc., will increase social learning and will strengthen the people's resilience and capacity to adapt [100]. It is also important to consider that agricultural adaptation does not only depend on making changes in agronomic practices and attitudes, but also on supportive functions provided by other farm enterprises and institutions both at micro and macro levels [101].…”
Section: From Perception To Adaptive Measures Regarding the Soil Erosmentioning
confidence: 99%
See 2 more Smart Citations
“…Nhemachena and Hassain (2007) found that lack of credit facilities, information on adaptation options and insufficient input are the major barrier to adapting any climate change adaptation options. Phuong, Biesbroek, Sen & Wals (2017)has mentioned several barriers to implement adaptation strategies including market price fluctuations, lack of skilled labor, lack of climate change information and lack of capacity to learn and apply techniques in their daily practice. Further, poor irrigation system is important barrier to secure agricultural production; and lack of institutional capacity to facilitate agriculture adaptation to household level created an important barrier to further adaptation.…”
Section: Hindrances To Adopt Available Adaptation Options Among Ruralmentioning
confidence: 99%